2016
DOI: 10.28945/3550
|View full text |Cite
|
Sign up to set email alerts
|

Using a Touch-Based, Computer-Assisted Learning System to Promote Literacy and Math Skills for Low-Income Preschoolers

Abstract: The use of touch-based technologies by young children to improve academic skills has seen growth outpacing empirical evidence of its effectiveness. Due to the educational challenges lowincome children face, the stakes for providing instructional technology with demonstrated efficacy are high. The current work presents an empirical study of the use of a touch-based, computerassisted learning system by low-income preschoolers. A description of the system's design is provided with attention to young children's in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…These findings are a strong contribution to the field of early childhood education, as it intersects with the use of technology in the classroom. These findings expand on the results of previous studies that demonstrate the benefits of CAI [11], and show that the impact of CAI is retained after the software is no longer being used.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These findings are a strong contribution to the field of early childhood education, as it intersects with the use of technology in the classroom. These findings expand on the results of previous studies that demonstrate the benefits of CAI [11], and show that the impact of CAI is retained after the software is no longer being used.…”
Section: Discussionsupporting
confidence: 86%
“…As a growing portion of the school-age population in the U.S. are EL and Hispanic students [3], it is more important than ever to close the achievement gap for these students. Research has shown that CAI has the potential to assist learning in young students [11], and that it can foster long term learning gains [13]. However, not all CAI interventions have been wholly positive [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an individualized curriculum increases students' flexibility, interactivity, and engagement, and it has been shown to improve young students' literacy skills [9]. CAI has been shown to benefit students at an early age: A study across 18 preschools gave students access to touchscreen desktops with interactive software which taught reading skills, and students who used the software scored higher in a standardized literacy test than those who did not [10].…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained from the study were similar to existing studies using CAI programs to improve knowledge for young children with disabilities. (Chai, Vail, & Ayers, 2015;Macaruso & Rodman, 2011;McManis & McManis, 2016;& Trotti, Hendricks, & Bledsoe, 2017). Four of the students, Cameron, Kylie, Hannah, and Sara, made some positive gains throughout the study, though gains were inconsistent.…”
Section: Discussionmentioning
confidence: 99%